The cost implications of less tight versus tight Control of Hypertension in Pregnancy (CHIPS Trial)novelty and significance - Ahmed, Rashid J.; Gafni, Amiram; Hutton, Eileen K.; Hu, Zheng Jing; Pullenayegum, Eleanor; von Dadelszen, Peter; Rey, Evelyne; Ross, Susan; Asztalos, Elizabeth; Murphy, Kellie E.; Menzies, Jennifer; Sanchez, J. Johanna; et al. (American Heart Association, 2016)
The CHIPS randomized controlled trial (Control of Hypertension in Pregnancy Study) found no difference in the primary perinatal or secondary maternal outcomes between planned “less tight” (target diastolic 100 mm Hg) and “tight” (target diastolic 85 mm Hg) blood pressure management strategies among women with chronic or gestational hypertension. This study examined which of these management strategies is more or less costly from a third-party payer perspective. A total of 981 women with singleton pregnancies and nonsevere, nonproteinuric chronic or gestational hypertension were randomized at 14 to 33 weeks to less tight or tight control. Resources used were collected from 94 centers in 15 countries and costed as if the trial took place in each of 3 Canadian provinces as a cost-sensitivity analysis. Eleven hospital ward and 24 health service costs were obtained from a similar trial and provincial government health insurance schedules of medical benefits. The mean total cost per woman–infant dyad was higher in less tight versus tight control, but the difference in mean total cost (DM) was not statistically significant in any province: Ontario ($30191.62 versus $24469.06; DM $5723, 95% confidence interval, −$296 to $12272; P=0.0725); British Columbia ($30593.69 versus $24776.51; DM $5817; 95% confidence interval, −$385 to $12349; P=0.0725); or Alberta ($31510.72 versus $25510.49; DM $6000.23; 95% confidence interval, −$154 to $12781; P=0.0637). Tight control may benefit women without increasing risk to neonates (as shown in the main CHIPS trial), without additional (and possibly lower) cost to the healthcare system.